(9, 10‐Dihydroxyoctadecyl)ammonium: A Structurally Unique Class of Clay Intercalable Surfactants. Issue 17 (22nd May 2015) - Jankovič, Luboš; Kronek, Juraj; Madejová, Jana; Hronský, Viktor
Abstract: The structurally unique clay–intercalable (9, 10‐dihydroxyoctadecyl)trimethylammonium (OH‐ODTMA) cationic surfactant was synthesized in two steps from commercially available oleylamine. Sodium montmorillonite was modified by a cation‐exchange reaction by using three different octadecyltrimethylamonium ODTMA‐based organic cations. Basal spacings, surfactant configuration, the interlamellar structure, and the thermal stability of the resulting organomontmorillonites were characterized by using X‐ray diffraction, IR spectroscopy, thermogravimetric analysis, and NMR spectroscopy techniques. Magic‐angle spinning 13 C NMR spectroscopy demonstrated the coexistence of ordered (all‐ trans ) and disordered ( gauche ) alkyl chain conformations. Deconvolution of the NMR spectra indicated that the conformational ordering of the surfactant molecules within the gallery of montmorillonite strongly depended on their orientation, the presence of functional groups, and the temperature. Relative to that found in ODTMA‐MT, the amount of gauche conformers was significantly higher in montmorillonite intercalated with the OH‐ODTMA cation and higher than that in the synthetic precursor, the oleyltrimethylammonium cation. Changes in the ordering of the organic cations were confirmed by FTIR spectroscopy with a distinct frequency shift in the CH stretching and overtone bands. The novel alkylammonium surfactant functionalized with two OH groups in the middle of the backbone represents a prospective ingredient for organoclay–polyurethane nanocomposites. Abstract : The structurally unique (9, 10‐dihydroxyoctadecyl)trimethylammonium (OH‐ODTMA) surfactant is synthesized from oleylamine. The OH‐ODTMA, ODTMA, and OLEYL‐TMA amphiphiles are successfully intercalated within clay galleries. The amount of gauche conformers is significantly higher in the novel OH‐ODTMA organoclay than in the ODTMA intercalate.